Thermal Performance Evaluation of a Synthetic Jet Heat Sink for Electronic Cooling - Chandratilleke, Tilak; Narayanaswamy, Ramesh; Jagannatha, Deepak (IEEE, 2011)
This paper presents a performance investigation on a highly effective heat removal technique for heat sinks in electronic cooling applications. This arrangement utilises a pulsating fluid jet mechanism known as synthetic jet, which is characterised by zero net fluid discharge through the jet orifice. The study uses an experimental rig comprising a high-frequency pulsating air jet that impinges on a heated surface to emulate the heat sink operation attached to an electronic device. The cooling characteristics of this jet are examined for a range of parametric conditions, including jet-impinging distance while evaluating the heat removal rates. The results indicate that the pulsating jet produces outstanding cooling performance at the heated surface with significant dependency of it on the jet-impinging distance. The study also assesses the interaction of a cross-flow fluid stream on the pulsed jet operation. It is observed that the cross-flow somewhat impedes the pulsed jet thermal performance. However, the pulsed jet, with or without cross flow, delivers an overall cooling ability that supersedes the standard flow-through heat sink performance. This technique provides highly enhanced surface cooling potential without incurring increased fluid pressure drop or requiring additional fluid circuit, which are significant advantages for high-powered heat sink design.